2015
DOI: 10.1364/ao.54.003868
|View full text |Cite
|
Sign up to set email alerts
|

Polarized structure color from thin dielectric gratings on a metal film

Abstract: Polarized structure color from thin dielectric gratings on an aluminum film is investigated. In the visible range, the −1st-order reflection of transverse electric (TE) light is higher than that of transverse magnetic (TM) light. Accordingly, the zeroth-order reflections for both polarizations behave distinctively such that TE-polarized light is chromatic while that for TM-polarized light is nearly white. Such chromatic and polarizing reflection predominantly comes from the Fabry-Perot interference between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…to optical switching [11][12][13][14], optical imaging [15,16], and optical anti-counterfeiting [17,18], making an invaluable contribution to modern nano-optics.…”
Section: Introductionmentioning
confidence: 99%
“…to optical switching [11][12][13][14], optical imaging [15,16], and optical anti-counterfeiting [17,18], making an invaluable contribution to modern nano-optics.…”
Section: Introductionmentioning
confidence: 99%
“…As period and depth of the optical structure of the photonic crystal are fixed, the structural color depends on the observation angle [34]. Studies show that photonic crystals with grating pattern are the favorable candidates for a variety of applications, not only due to their compact structures, simple fabrication process and excellent spectral characteristics, but also because reflection wavelength and observation angle are closely connected [57]. At present, nanoimprint lithography (NIL) and self-assembly are the two main methods to prepare photonic crystals with grating pattern [811].…”
Section: Introductionmentioning
confidence: 99%
“…The metamaterial perfect absorbers (MMPA) [25]- [30] are one kind of plasmonic metamaterials with nearly 100% absorption at the certain wavelength based on the excitation surface plasmon resonances (SPR) and localized surface plasmon resonances (LSPR). It's found that the selective absorption of MMPA can manipulate the reflection spectrum to generate different colors by changing the nanostructure [31]- [33]. Due to the single-band characteristic of most MMPA, the reflective artificial structure colors are usually not the red, green and blue (RGB) but their complementary colors: cyan, magenta, and yellow (CMR).…”
Section: Introductionmentioning
confidence: 99%
“…The 1D polarization-controllable MMPA (such as 1D grating) behaves like a 'switch' because it excites only the resonant modes for TE-polarized light [44]- [48]. Cui et al have reported the polarization-controllable structure color based on 1D grating MMPA, which demonstrates some color for TE-polarized incident white light, while white for TM-polarized incident white light [33]. In order to gradually changing the structural color from one color to another (not white), the absorption peak wavelength must be shifted with polarization.…”
Section: Introductionmentioning
confidence: 99%